Atorvastatin protects against postoperative neurocognitive disorder via a peroxisome proliferator-activated receptor-gamma signaling pathway in mice. Issue 5 (May 2020) - Yang, Yinan; Wei, Changwei; Liu, Jinhu; Ma, Danxu; Xiong, Chao; Lin, Dandan; Wu, Anshi
Objective: Postoperative neurocognitive disorder (PND) is a main complication that is commonly seen postoperatively in elderly patients. The underlying mechanism remains unclear, although neuroinflammation has been increasingly observed in PND. Atorvastatin is a pleiotropic agent with proven anti-inflammatory effects. In this study, we investigated the effects of atorvastatin on a PND mouse model after peripheral surgery. Material and methods: The mice were randomized into five groups. The PND models were established, and an open field test and fear condition test were performed. Hippocampal inflammatory cytokine expression was determined using ELISA. Peroxisome proliferator-activated receptor-gamma (PPARγ) expression in the hippocampus was tested using qRT-PCR and western blot analysis. Results: On day 1 after surgery, inflammatory cytokines such as tumor necrosis factor-α, interleukin-1β, and interleukin-6 showed a significant increase in the hippocampus, with prominent cognitive impairment. Atorvastatin treatment improved cognitive function in the mouse model, attenuated neuroinflammation, and increased PPARγ expression in the hippocampus. However, treatment with the PPARγ antagonist GW9662 partially reversed the protective effects of atorvastatin. Conclusions: These results indicated that atorvastatin improves several hippocampal functions and alleviates inflammation in PND mice after surgery, probably through a PPARγ-involved signaling pathway.